Exploration of Internal and External Factors Influencing Difficulties in Learning Arabic at Madrasah Aliyah - Rohanda Rohanda; Siti Shabrina Nur Ghassani; Yasmin Nurfadhila Nazmi (Gunung Djati Conference Series, 2026)
Arabic language learning at Madrasah Aliyah continues to face serious challenges, characterized by students’ limited vocabulary mastery, low speaking fluency, and difficulties in comprehending texts. These challenges are influenced not only by individual learner factors but also by diverse learning environment conditions. This study aims to comprehensively explore the interaction between internal factors, including motivation, basic linguistic competence, learning strategies, psychological conditions, and cognitive abilities, and external factors such as teacher competence, teaching methods, availability of learning media, family support, facilities, and curriculum policies. Using a descriptive qualitative approach, data were collected through classroom observations, in-depth interviews with students and teachers, and analysis of instructional documents. The findings indicate that internal factors often serve as the initial trigger of learning difficulties, yet the quality of the learning environment determines whether these difficulties improve or develop into chronic obstacles. Monotonous teaching methods, less contextual learning materials, and limited opportunities for practice were found to reinforce the negative impact of internal factors. Conversely, appropriate external interventions, such as varied teaching methods, audio-visual media, and strong support from both family and school, can significantly enhance students’ motivation and skills. These findings affirm that difficulties in learning Arabic are multidimensional and interrelated, requiring effective interventions that integrate the strengthening of students’ internal strategies with systemic improvements in external aspects. This study provides a conceptual foundation for developing more adaptive instructional models and policies to improve the quality of Arabic language education at Madrasah Aliyah.